Relationship between Situational Leadership Style and Employee Performance RSM Ahmad Dahlan Kediri City - Percunda, Alita Dewi; Afrianingrum, Anisa Laras; Laksono, Adi; Sulistyawan, Agus; Putri, Lovia Ayu Nenda Rifqy (Universitas Mandala Waluya, 2025)
Section heads in the Ahmad Dahlan Hospital Inpatient Installation in Kediri apply a significant situational leadership style with management functions. Objective: To analyze the relationship between situational leadership style and employee performance of RSM Ahmad Dahlan Kota Kediri. Quantitative correlation is the method in this study, then a cross-sectional design that uses a questionnaire to measure situational leadership style and employee performance at the Inpatient Installation of RSM Ahmad Dahlan Kota Kediri. Using the saturated sampling technique, which means that all members of the population are used as samples, namely 76 people in the Inpatient Installation. Descriptive analysis and correlation analysis were carried out using the SPSS application. The majority of respondents were female (82%), with most ages between 20-35 years (83%), and the length of work was mostly 6-10 years (38%). The result of descriptive analysis for the situational leadership style variable is 4.54 (SD .459), with the highest sub-variable being 4.39 (SD .474), and for the employee performance variable, 4.33 (SD .436). The results of the correlation test between situational leadership style and all its sub-variables are related to employee performance (sig .000), with the largest correlation coefficient selling (r .781). Situational leadership style is related to employee performance, and RSM Ahmad Dahlan Kediri City should improve the situational leadership style of existing superiors.